2020
DOI: 10.1093/ecco-jcc/jjz203.510
|View full text |Cite
|
Sign up to set email alerts
|

P381 Use of ustekinumab in Crohn’s disease: Singapore largest single-centre experience

Abstract: Background Ustekinumab is the latest therapeutic option for Crohn’s disease (CD). Efficacy and safety outcomes of its use in the Asia CD population, however, have not been reported. Methods Patients with CD who received minimum 14 weeks of UST were included. The primary outcome was the percentage of patients who achieved remission by global physician assessment, GPA [defined by Steroid Free Remission (Harvey Bradshaw Index ≤4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A previous study on the experience of UST in Singapore showed favorable outcomes, comparable to western populations. 9 In this study, we showed that DI was effective in 38% of both CD and UC patients in our cohort. This echo published data, which showed that DI was effective in about 40-50% of IBD patients.…”
Section: Discussionsupporting
confidence: 49%
“…A previous study on the experience of UST in Singapore showed favorable outcomes, comparable to western populations. 9 In this study, we showed that DI was effective in 38% of both CD and UC patients in our cohort. This echo published data, which showed that DI was effective in about 40-50% of IBD patients.…”
Section: Discussionsupporting
confidence: 49%
“…A total of 63 studies (including 8529 patients) met the inclusion criteria and were finally included in the systematic review and meta-analysis ( Figure 1 ) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Only one study focused exclusively on naïve patients [ 55 ], and in three studies, prior biologic exposure was not reported. Only three studies (4.8%) included paediatric patients [ 54 , 59 , 63 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In 2020, a study trial involving 22 Singapore-Asia cohort demonstrated that the safety and efficacy of ustekinumab were comparable to Western data. 25 Even more recently, tofacitinib (Janus kinase inhibitor) was also granted local regulatory approval in 2021 for moderate to active UC patients that had inadequate/lost response or intolerant to either conventional therapy or a biologic agent.…”
Section: Healthcare Economics Of Ibd In Singaporementioning
confidence: 99%
“…In addition, other new IBD treatment includes ustekinumab (a monoclonal antibody targeting IL-12 and IL-23) that had obtained the Health Science Authority regulatory approval in February 2018 for the treatment of moderate to severely active CD adult patients that had failed or intolerant to immunomodulators or corticosteroids. In 2020, a study trial involving 22 Singapore-Asia cohort demonstrated that the safety and efficacy of ustekinumab were comparable to Western data [ 25 ]. Even more recently, tofacitinib (Janus kinase inhibitor) was also granted local regulatory approval in 2021 for moderate to active UC patients that had inadequate/lost response or intolerant to either conventional therapy or a biologic agent.…”
Section: Healthcare Economics Of Ibd In Singaporementioning
confidence: 99%